Elevated serum trem-1 levels are associated with das28 and periodontitis in rheumatoid arthritis - İnanç, Nevsun; Mumcu, Gonca; Can, Meryem; Direskeneli, Haner; Bostancı, Nagihan (BMJ Publishing Group, 2019)
Background: The Triggering Receptor Expressed on Myeloid cells 1(TREM-1) along with its putative ligand peptidoglycan recognition protein1 (PGLYRP1) are involved in the propagation of the inflammatoryresponse to microbial exposure(1). Periodontal disease (PD) has beensuggested as an environmental risk factor for rheumatoid arthritis (RA),yet further studies are required to dissect the mechanisms underlying theassociation between the two(2).
Conference: Annual European Congress of Rheumatology (EULAR) Location: Madrid, SPAIN Date: JUN 12-15, 2019
Keywords: TREM-1; PGLYRP1